2020
DOI: 10.1109/access.2020.2970485
|View full text |Cite
|
Sign up to set email alerts
|

Color Space Transformation and Multi-Class Weighted Loss for Adhesive White Blood Cell Segmentation

Abstract: White blood cells (WBCs) are the cells of immune system, protecting against infective diseases and invasion of viruses and bacteria. Their aberrant number, both abnormal increase and decrease, is a sign of an ongoing pathology, a precise evaluation of their number is of the utmost importance as the first step of assessing a potential disease. In blood cell microscopic images, since red blood cells and platelets are similar in color with WBCs, and WBCs are partially adhesive, WBC segmentation for counting is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Their results showed that the highest segmentation accuracy was 96.92% using the S component of the HSV color space. Moreover, Li et al [56] proposed a weighted cross-entropy loss function based on class weight and distance transformation weight for deep learning using U-Net for the WBC segmentation using ALL-IDB1, which resulted in 94.92% segmentation accuracy without data augmentation. In addition, our counting accuracy was 93.7% using the entire ALL-IDB dataset, which is 12.7% higher than the accuracy reported by Mahmood et al [57], where color space conversion and Hough transform were used for WBC detection.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the highest segmentation accuracy was 96.92% using the S component of the HSV color space. Moreover, Li et al [56] proposed a weighted cross-entropy loss function based on class weight and distance transformation weight for deep learning using U-Net for the WBC segmentation using ALL-IDB1, which resulted in 94.92% segmentation accuracy without data augmentation. In addition, our counting accuracy was 93.7% using the entire ALL-IDB dataset, which is 12.7% higher than the accuracy reported by Mahmood et al [57], where color space conversion and Hough transform were used for WBC detection.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the developed GFS Extreme-Net model consumes more time for labeling, and also it is very difficult to identify the specific extreme points that reflects the best geometric features of a target. Additionally, H. Li, X. Zhao, A. Su, H. Zhang, J. Liu, and G. Gu, [17] developed a weight map on the basis of distance transformation weight and class weight to improve the ability of loss function in U-Net for effectively learning the cell border feature. The experimental results showed that the developed model achieved better performance in white blood cell segmentation on the ALL-IDB1 database.…”
Section: Literature Surveymentioning
confidence: 99%
“…Therefore, the HSV color information [22] is used to process wood images before classification. The wood color ranges in the H, S, and V channels can be used for removing the background and stains simultaneously [23].…”
Section: Image Preprocessingmentioning
confidence: 99%